FURTHER DEVELOPMENT OF THE FIELD OF FRUIT AND VEGETABLE AND VITICULTURE IN OUR REPUBLIC - Khodjamov Odil Kuysinovich; Nаzаrov Ibrohim Hаsаn ugli (Journals Park Publishing, 2024)
This article presents the organization of clusters in the development of horticulture and viticulture and the analysis of the production of rice products in agriculture.
Keywords: gardening, viticulture, greenhouse, cluster, vineyard, horticulture.